The fertilization of fields in the northern half of France (600 BCE−500 CE), approached by N isotope analyses of cereal remains - Ben Makhad, Sammy; Balasse, Marie; Fiorillo, Denis; Malrain, François; Aguilera, Mònica; Matterne, Véronique (Frontiers in Environmental Archaeology, 2024)
The present study investigates organic fertilisation techniques at the crop scale, through nitrogen isotope analyses (δ 15 N), which are used as an indicator of soil fertility and the use of fertilising organic matter (such as manure). The study was conducted on a sample of 124 crop remains, consisting of 6490 archaeological cereal grains (emmer wheat, spelt wheat, free-threshing wheats and hulled barley) recovered from 68 archaeological sites located across the northern half of France, dating between the 6 th century BC and the 5 th century AD. To evaluate δ 15 N values of archaeological cereals in terms of fertilisation, we compared published experimental data of modern cereals (grown under different fertilisation regimes) for temperate Europe with published and new isotopic analyses of archaeological deer bone collagen from northern France as a proxy for wild unfertilised flora. Discriminant analysis and ordinal logistic regression were used for the classification of archaeological grain δ 15 N values by degree of fertilisation.The results show that field fertilisation was a common practice in Gaul, generally on a moderate scale. However, variations are observed in fertilisation use within farms, with some intensively fertilised fields and others with less or no fertilisation at all. In addition, regional differences emerged, particularly in the chalky Champagne region, where farmers used significantly less fertiliser than in other regions. Chronological trends over the studied period remain unclear. Disparities in the fertilisation levels of different cereal species are noted. The δ 15 N values show considerable variations in soil fertility for barley and spelt, while fertilisation regimes for freethreshing wheats and emmer only diversified during the 2 nd and 1 st centuries BC. These observations concur with the extensification of cultivation as inferred from carpological and weed ecology studies. Interspecific variations can also be seen in treatments applied to free-threshing wheats, which were fertilised much more commonly than the other three cereals from the 1 st c. BC/1 st c. AD, when these crops were in full expansion.